Dynamic response analysis for submerged floating tunnel with anchor-cables subjected to sudden cable breakage. (May 2018) - Xiang, Yiqiang; Chen, Zhengyang; Yang, Ying; Lin, Heng; Zhu, Sheng
Abstract: Anchor-cables are critical bearing components of the submerged floating tunnel (SFT). As the accidental cable-breakage incident will seriously threaten the public safety, this paper investigates the global dynamic response of a SFT subjected to an abrupt anchor-cable failure by focusing on the post-breakage behavior. Firstly, an approximate theoretical approach is proposed, in which the analysis model of SFT is simplified and the alternate load path method (AP method) is adopted to simulate the cable-breakage process. Then, the differential equations of the SFT tube are established based on the Hamilton principle, and solved through the fourth order Runge-Kutta method. A finite element analysis in ABAQUS is also performed as a verification of the theoretical results, in which the VUSDFLD subroutine and ABAQUS/Aqua is employed to simulate the stiffness loss of the cable and apply the fluid loads respectively. A good agreement exists between the simplified theoretical model and FE simulation. Finally, the effects of some key parameters are discussed, such as the gravity-buoyance ratio and the damping ratio of the SFT, the breakage time and position of the broken cable, etc. The results show that the structural vibration is intensive after the sudden cable breakage. Also, the remaining anchor-cables close to the cable-loss position are most affected by the cable rupture. The change of gravity-buoyance ratio and damping ratio have notable effects on structural deformation. The SFT is most unfavorable when the cable breakage happens at the mid-span or near the two ends of the tunnel. The vibration amplitude attenuates significantly with the increase of the failure time of anchor-cable. Highlights: Global dynamic response of the submerged floating tunnel (SFT) under a sudden anchor-cable breakage is investigated. An approximate theoretical approach is proposed, in which the SFT and the process of cable failure is simplified. Finite element analysis in ABAQUS is performed as a verification of the theoretical model. The influences of some key parameters on the structural dynamic behaviors are discussed.